Efektivitas Model Pembelajaran Knisley dengan Teknik Storytelling dalam Mengatasi Math Anxiety dan Meningkatkan Minat Belajar - Aniq Darmayanti; Putriaji Hendikawati (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Mathematics is a fundamental subject that develops students' logical reasoning and problem-solving skills. However, many students experience math anxiety, which negatively affects their interest in learning. This study aimed to examine the effectiveness of the Knisley learning model integrated with the storytelling technique in reducing math anxiety and improving students' learning interest. A quantitative approach with a quasi-experimental method and a Pretest–Posttest Control Group Design was employed. The study involved 60 students of Walisongo Vocational High School, Semarang, consisting of 30 students in the experimental group and 30 students in the control group. Data were collected using math anxiety and learning interest questionnaires and analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, Wilcoxon Signed-Rank Test, Mann–Whitney U Test, and effect size analysis. The findings revealed that students in the experimental group showed a significantly greater reduction in math anxiety and improvement in learning interest than those in the control group (p < 0.001). Furthermore, the effect size values of 0.60 for math anxiety and 0.62 for learning interest indicate a large practical effect of the intervention. These findings suggest that integrating the Knisley learning model with the storytelling technique provides an effective instructional approach to creating a more engaging mathematics learning environment, reducing students' math anxiety, and fostering greater interest in learning mathematics.